2010
DOI: 10.1590/s1984-29612010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico da Leishmaniose Visceral Canina pelas técnicas de imunoistoquímica e PCR em tecidos cutâneos em associação com a RIFI e ELISA-teste

Abstract: ResumoO objetivo deste trabalho foi avaliar as técnicas de imunoistoquímica (IMIQ) e de PCR (Reação em Cadeia da Polimerase) em tecidos cutâneos para o diagnóstico da Leishmaniose Visceral Canina (LVC) e compará-los com os exames parasitológicos em tecidos corados histoquimicamente (hematoxilina-eosina, HE) e com testes sorológicos, como a Reação de Imunofluorescência Indireta (RIFI) e ensaio imunoenzimático (ELISA). Dos 34 cães naturalmente infectados, classificados em assintomáticos, oligossintomáticos e pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
1
5
1
4
Order By: Relevance
“…These findings are in agreement with de Queiroz et al (2010) who reported that 87.5 % of asymptomatic dogs showed seronegativity in two different tests, while PCR of skin samples revealed 100 % positive results.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with de Queiroz et al (2010) who reported that 87.5 % of asymptomatic dogs showed seronegativity in two different tests, while PCR of skin samples revealed 100 % positive results.…”
Section: Discussionsupporting
confidence: 93%
“…This fact may be related to the parasite load in symptomatic animals (Lima et al 2010), thus making it easier to diagnose in this group of animals as proved by Queiroz et al (2010) when using several methodologies for VL diagnosis in dogs with and without clinical symptoms. For Maia et al (2009), the infection difference of diverse organs of the same animal may be associated to the potential parasite load and related with the local immune response of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…infection in dogs at several clinical stages and our results showed variation in sensitivity between the primer sets used. The sensitivity of each technique may vary over the course of evolution of the disease and between individuals; therefore, a combination of serological and molecular tests may be necessary to correct the diagnosis (ASSIS et al, 2010;NUNES et al, 2007;QUEIROZ et al, 2010;SILVA et al, 2014). In addition, it has been recommended that the diagnosis of this disease should be based on clinical signs and on the epidemiological characteristics of the region, which may contribute towards correctly identifying truly positive animals (SILVA et al, 2014).…”
Section: Discussionmentioning
confidence: 99%